Machado de Assis's literacy relics (Tempo e Argumento, 2010)
Relíquias de Casa Velha was the last book organized by Machado de Assis, in which the writer wanted to air his rooms by exposing the heirlooms from a past he lived and witnessed. Through the short stories and other non-fictional writings, a relation between the imperial past and the republican present is noticeble. This paper intends to discuss this very relation through a careful reading of the short stories, problematizing the values highlighted by Machado de Assis for his time, such as patriotism, modernity, progress and work, which would be the empire relics for the republic.
Keywords: brasilian empire; brasilian republic; slavery; progress